An Identification of Student Creativity in Stage Makeup Courses - Mitra Lusiana; Agusti Efi; Giatman Giatman (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2021)
This study aims to describe factually about Student Creativity in the Stage Makeup course, Department of Make-Up and Beauty, Faculty of Tourism and Hospitality, Padang State University. This study uses a qualitative method. Research data collection was carried out by observation, interviews and documentary studies. Data were analyzed using qualitative analysis. Key informants are students in make-up courses and supporting informants are lecturers of stage make-up. The results showed that the creativity of the students in the Makeup and Beauty Study Program at the Faculty of Tourism and Hospitality, Padang State University was not optimal because the students did not demonstrate enough to realize high creativity. Learning runs effectively and efficiently but still does not lead to creative learning. Creative products produced by students are not satisfactory.